Validity of the total SOFA score in patients ≥ 80 years old acutely admitted to intensive care units: a post-hoc analysis of the VIP2 prospective, international cohort study - Kamil Polok; Jakub Fronczek; Zbigniew Putowski; Marcelina Czok; Bertrand Guidet; Christian Jung; Dylan de Lange; Susannah Leaver; Rui Moreno; Hans Flatten; Wojciech Szczeklik (Annals of Intensive Care, 2023)
Abstract Background Little is known about the performance of the Sequential Organ Failure Assessment (SOFA) score in older critically ill adults. We aimed to evaluate the prognostic impact of physiological disturbances in the six organ systems included in the SOFA score. Methods We analysed previously collected data from a prospective cohort study conducted between 2018 and 2019 in 22 countries. Consecutive patients ≥ 80 years old acutely admitted to intensive care units (ICUs) were eligible for inclusion. Patients were followed up for 30 days after admission to the ICU. We used logistic regression to study the association between increasing severity of organ dysfunction and mortality. Results The median SOFA score among 3882 analysed patients was equal to 6 (IQR: 4–9). Mortality was equal to 26.1% (95% CI 24.7–27.5%) in the ICU and 38.7% (95% CI 37.1–40.2%) at day 30. Organ failure defined as a SOFA score ≥ 3 was associated with variable adjusted odds ratios (aORs) for ICU mortality dependant on the organ system affected: respiratory, 1.53 (95% CI 1.29–1.81); cardiovascular 1.69 (95% CI 1.43–2.01); hepatic, 1.74 (95% CI 0.97–3.15); renal, 1.87 (95% CI 1.48–2.35); central nervous system, 2.79 (95% CI 2.34–3.33); coagulation, 2.72 (95% CI 1.66–4.48). Modelling consecutive levels of organ dysfunction resulted in aORs equal to 0.57 (95% CI 0.33–1.00) when patients scored 2 points in the cardiovascular system and 1.01 (0.79–1.30) when the cardiovascular SOFA equalled 3. Conclusions Different components of the SOFA score have different prognostic implications for older critically ill adults. The cardiovascular component of the SOFA score requires revision.